KREATIVITAS PENGOLAHAN LIMBAH PLASTIK PADA WARGA 3 ILIR PALEMBANG - Andi Surya Sapada; Mutia Mawardah (Bajang Institute, 2023)
Tiga ilir is one of the sub-districts in Ilir Timur II sub-district, Palembang, South Sumatra, has an area of ​​0.60 km² which is divided into 10 RWs and also divided into 51 RTs. Because it is relatively far from the center of Palembang city, with a dense population and also a lack of jobs, the people of Tiga Ilir are required to be more able to think ahead to increase their economic rate. improve their economy. Creativity by Chaplin (1999, p.117) is defined as the ability to produce new forms in art or in machinery or in solving problems with new methods. Coleman and Hammen (Rakhmat, 1991, p. 74) defines creative thinking as the ability to think that produces new products, concepts, understandings, discoveries and the art of work. The purpose of this field work practice (PKL) is (1) The benefits of this program are to utilize used goods, including bottles that are no longer used, to become goods that have artistic and economic value, besides being able to reduce waste in the community. (2) The innovation aspect in this program is how the people of Tiga Ilir can utilize used goods to become quite profitable business opportunities. (3) In this program, it is hoped that a creative spirit will emerge within the Tiga Ilir community so that they are able to improve their economy. The method used in this field work practice is the planning method. The target in this program is the residents of Palembang's three ilir. Data collection techniques using observation, interviews and documentation. The results of field work practices: (1) Increasing the economy of Tiga Ilir residents (2) Creating more jobs for the surrounding community (3) Using plastic waste as a raw material for making products to reduce the impact of plastic waste. (4) Being a creative business with modern technology that is environmentally friendly (5) Playing an active role in building partnerships with the government, private sector and the community (6) being consistent in raising public awareness of the importance of managing plastic waste for the environment with the 3R principle (Reduce, Reuse, Recycle). (1) Increasing the economy of Tiga Ilir residents (2) Creating more jobs for the surrounding community (3) Using plastic waste as a raw material for making products to reduce the impact of plastic waste. (4) Being a creative business with modern technology that is environmentally friendly (5) Playing an active role in building partnerships with the government, private sector and the community (6) being consistent in raising public awareness of the importance of managing plastic waste for the environment with the 3R principle (Reduce, Reuse, Recycle). (1) Increasing the economy of Tiga Ilir residents (2) Creating more jobs for the surrounding community (3) Using plastic waste as a raw material for making products to reduce the impact of plastic waste. (4) Being a creative business with modern technology that is environmentally friendly (5) Playing an active role in building partnerships with the government, private sector and the community (6) being consistent in raising public awareness of the importance of managing plastic waste for the environment with the 3R principle (Reduce, Reuse, Recycle)